“TO PROHIBIT THEM ALL WITHOUT EXCEPTION ENTERING OUR REALM…”: NAQSHBANDIYA-KHALIDIYA IN KURDISTAN AND DAGESTAN - Pobedonosceva-Kaa, Anzelika Olegovna (History, Archeology and Ethnography of the Caucasus, 2023)
The article deals with the history of contacts between the mountain peoples of the Caucasus and the Kurds of the Ottoman Empire and Persia in the 18th - 19th centuries. Using diplomatic and other official documents, as well as memoirs and summarizing the results of previous studies, the article analyzes the dynamics and characteristics of these contacts in the context of geopolitical rivalry of several empires in the region. The proximity of Dagestan and Kurdistan, their location at the crossroads of merchants and pilgrims led not only to the formation of diverse confessional communities, but also to the strengthening of trans-regional ties as a result of the spread of spiritual practices, in particular Sufi ones. Kurdish-Caucasian ties played a significant role in the emergence and strengthening in the Caucasus of the Khalidian branch of the Naqshbandi tariqa, one of the most influential Sufi traditions in the Islamic world. The territorial expansion of the Russian Empire in the first third of the 19th century led to its establishing control over a number of territories with Kurdish population, while the fears of the Russian authorities in connection with the Kurdish-Dagestani interaction through the “Khalidian” channel during the years of the Caucasian War became one of the reasons for the Russian authorities to apply administrative measures against the Kurds, which laid the foundation for Russia’s future policy towards the Kurds. At the same time, the political significance of cross-border solidarity turned out to be temporarily limited, which proves the complicated nature of cross-border interaction even within the framework of religious movements sharing a single ideology.